An implicit priming intervention alters brain and behavioral responses to high-calorie foods: a randomized controlled study. Issue 4 (14th January 2022) - Legget, Kristina T; Cornier, Marc-Andre; Erpelding, Christina; Lawful, Benjamin P; Bear, Joshua J; Kronberg, Eugene; Tregellas, Jason R
ABSTRACT: Background: Conditioned food cues (e.g., smell, sight) can affect intake of foods associated with those cues, regardless of homeostatic need. As such, altering automatic associations with food cues could support weight loss or maintenance efforts by affecting the salience of those cues and the effort required to resist consumption. Objectives: This study investigated neuronal and behavioral effects of an implicit priming (IP) intervention, in which negatively valenced images were paired with high-calorie foods and positively valenced images with low-calorie foods. Priming images were presented immediately before food images, but below conscious perception (20 ms). We hypothesized that this evaluative conditioning approach could alter food cue responses by modifying affective associations. Methods: The final sample included 41 adults with BMI ≥25 kg/m 2 ( n = 22, active IP; n = 19, control IP). In control IP, food images were primed with neutral, scrambled images. Participants completed a visual food cue task during fMRI, both before and after IP. To determine the replicability of prior behavioral findings, food image ratings were completed before and after IP as a secondary outcome. Results: In a whole-brain analysis, reduced dorsolateral prefrontal cortex (dlPFC) response to high-calorie foods was observed after active compared with control IP ( t = 4.93, P = 0.033). With a region of interest analysis, reduced response to high-calorie foods in active compared with control IP was also observed in the striatum ( t = 2.40, P = 0.009) and insula ( t = 2.38, P = 0.010). Active compared with control IP was associated with reduced high-calorie food ratings ( F = 4.70, P = 0.038). Conclusions: Reduced insula and striatum response to high-calorie foods after active compared with control IP suggests effectiveness of IP in altering food cue salience. Reduced dlPFC response to high-calorie foods after active compared with control IP may reflect fewer attentional resources being directed to those images and reduced engagement of inhibitory processes. This trial was registered at clinicaltrials.gov as NCT02347527.